Antibiotic-resistant bacteria in hospital wastewater treatment plant effluent and the possible consequences of its reuse in agricultural irrigation - Mehanni, Magda M.; Gadow, Samir I.; Alshammari, Fahdah Ayed; Modafer, Yosra; Ghanem, Kholoud Z.; El-Tahtawi, Noha Fathy; El-Homosy, Rania F.; Hesham, Abd El-Latif (Frontiers in Microbiology, 2023)
Antibiotic residues in treated hospital wastewater effluents constitute a major environmental concern since they resist various wastewater treatment processes. The emergence and spread of multi-drug-resistant bacteria, that cause public health problems, are therefore always a major concern. Aims and objectives of this study were mainly to characterize the chemical and microbial properties of the hospital effluent of WWTP before discharge to environment. Special attention was paid to the presence of multiple resistance bacteria and the effects hospital effluent reuse in irrigation on zucchini as an economically important plant. The risk of cell free DNA carrying antibiotic resistance genes that contained in the hospital effluent as a long-lasting hazard had been discussed. In this study, 21 bacterial strains were isolated from the effluent of a hospital wastewater treatment plant (WWTP). Isolated bacteria were evaluated for multi-drug resistance ability against 5 antibiotics (Tetracycline, Ampicillin, Amoxicillin, Chloramphenicol and Erythromycin) at a concentration of 25 ppm. Out of them, three isolates (AH-03, AH-07 and AH-13) were selected because they recorded the highest growth in presence of tested antibiotics. Selected isolates were identified using 16S rRNA gene sequence homology as Staphylococcus haemolyticus (AH-03), Enterococcus faecalis (AH-07) and Escherichia coli (AH-13). Their susceptibility to ascending concentrations of tested antibiotics indicated that they were all susceptible at a concentration above 50 ppm. Results of greenhouse experiment regarding the effect of hospital WWTP effluent reuse on zucchini plant fresh weights compared to that irrigated with fresh water indicated that the former recorded limited increase in total fresh weights (6.2 g and 5.3 g/plant respectively). Our results demonstrated the low impact of reuse of Hospital WWTP effluent in agriculture irrigation compared to its greater risk in transferring multiple antibiotic bacteria and antibiotic resistance genes to soil bacteria through natural transformation.